A Case Presentation and Treatment Review on Novel COVID 19 - Jha, Ambika Nand; Shah, Akshay H; Trivedi, Upama N (Journal of Current and Advance Medical Research, 2021)
SARS-COV 2 Is causative agent of COVID 19, just few month ago was foreign to us and now spreading its routes well in India. Starting with one case As of August 25, 2020 in India 3167323 positive cases have been reported. coronavirus is beta form of SARS-CoV-2 belong to family of Coronaviridae. A 44-year-old man, who lives in Kolakata, West Bengal, Working in a travel agency. He came To OPD with complaint of fever, Throat Infection, Multiple joint and muscle pain, Cough. A SARS-CoV-2 Reverse transcriptase polymerase chain reaction (RTPCR) test was positive. He was being treated & Monitored in Home isolation with high dose oral ascorbic acid, hydroxychloroquine, azithromycin and Zinc acetate. This Article aimed to Case Presentation And Treatment Review of Novel COVID 19. Journal of Current and Advance Medical Research, January 2021;8(1):75-77